Caspase-(8/3) activation and organ inflammation in a rat model of resuscitated hemorrhagic shock: A role for uric acid. Issue 3 (March 2019) - Gilbert, Kim; Rousseau, Guy; Bouchard, Caroline; Dunberry-Poissant, Sophie; Baril, Frédérique; Cardinal, Anne Marie; Khazoom, François; Vega, Melissa Aubin; Brochiero, Emmanuelle; Charbonney, Emmanuel
Abstract : BACKGROUND: Multiple organ failure can develop after hemorrhagic shock (HS). Uric acid (UA) is released from dying cells and can be proinflammatory. We hypothesized that UA could be an alternative mediator of organ apoptosis and inflammation after HS. METHODS: Ventilated male Wistar rats were used for the HS model. Two durations of shock (5 minutes vs. 60 minutes) were compared, and shams were instrumented only; animals were resuscitated and observed for 24 hours/72 hours. Caspases-(8/3), myeloperoxidase (MPO), TNF-α were measured in lungs and kidneys. Plasma UA and cytokine (IL-1β, IL-18, TNF-α) were measured. A second set of animals were randomized to vehicle versus Rasburicase intraperitoneal intervention (to degrade UA) during resuscitation. Another group received exogenous UA intraperitoneally without HS. Measures mentioned above, in addition to organs UA, were performed at 24 hours. In vitro, caspases-(8/3) activity was tested in epithelial cells exposed to UA. RESULTS: Hemorrhagic shock increased organ (kidney and lung) TNF-α, MPO, and caspases activity in various patterns while caspase-8 remained elevated over time. Hemorrhagic shock led to increased plasma UA at 2 hours, which remained high until 72 hours; TNF-α and IL-18 were elevated at 24 hours. The exogenous UA administration in sham animals reproduced the activation of caspase-8 and MPO in organs, and TNF-α in the lung. The increased plasma and organ UA levels, plasma and lung TNF-α, as well as organ caspase-(8/3) and MPO, observed at 24 hours after HS, were prevented by the administration of Rasburicase during resuscitation. In vitro, soluble UA induced caspases-(3/8) activity in epithelial cells. CONCLUSION: Uric acid is persistently high after HS and leads to the activation of caspases-8 and organ inflammation; these can be prevented by an intervention to degrade UA. Therefore, UA is an important biomarker and mediator that could be considered a therapeutic target during HS resuscitation in human. Abstract : Supplemental digital content is available in the text.